2020
DOI: 10.1007/s11103-020-01041-8
|View full text |Cite|
|
Sign up to set email alerts
|

Integrative transcriptomics reveals genotypic impact on sugar beet storability

Abstract: Key message An integrative comparative transcriptomic approach on six sugar beet varieties showing different amount of sucrose loss during storage revealed genotype-specific main driver genes and pathways characterizing storability. Abstract Sugar beet is next to sugar cane one of the most important sugar crops accounting for about 15% of the sucrose produced worldwide. Since its processing is increasingly centralized, storage of beet roots over an extended time has become necessary. Sucrose loss during stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 121 publications
(146 reference statements)
2
17
0
Order By: Relevance
“…For vascular cells, there is no size reference yet. The cell sizes measured in the storage parenchyma were on the lower end of the range reported in other studies [9,26,27]. This was mainly in uenced by the fact that in the presented work ow, only the rst 6 mm from the periphery to the center were considered.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…For vascular cells, there is no size reference yet. The cell sizes measured in the storage parenchyma were on the lower end of the range reported in other studies [9,26,27]. This was mainly in uenced by the fact that in the presented work ow, only the rst 6 mm from the periphery to the center were considered.…”
Section: Discussionmentioning
confidence: 67%
“…So far, the underlying shape and the real cell size distribution is unknown for sugar beet roots. We have refrained from correcting the measured cell size, as in other published studies of sugar beet roots, no adjustment was made either for real cell size [5,9,10,12,26,27]. But as the possible error is the same for all genotypes (or other treatments) a comparison of those will always be correct…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, deciphering key factors associated with good storability is crucial because these factors can be used as biomarkers, e.g., to screen available varieties or to optimize breeding programs by including marker-assisted selection (MAS) targeting prolonged storability. Several single-omics studies have already been performed to address the above described problems [ 51 53 ]. However, a multi-omics analysis targeting this research question has not yet been performed.…”
Section: Resultsmentioning
confidence: 99%
“…Although changes in the composition of the cell wall and pathogen invasion also contribute to this loss, respiration is the predominant cause. Numerous studies have been conducted to look into how delivery delays affect the characteristics of sugar beets (Tsialtas & Maslaris, 2013;Al-Jbawi et al, 2015;El-Syiad, 2016, Hoffmann & Schnepel, 2016Madritsch et al, 2020). Abd El-Rahman & El-Geddawy, 2019) showed that sugar beet manufacturing at 210 days gives the lowest percentage of nitrogen substance, thus sugar percentage increased in comparison with early periods.This study was carried out to evaluate chemical and quality parameters of different size of sugar beet roots storage at different days and harvest age with different time of working or processing juice season.…”
Section: Introductionmentioning
confidence: 99%